Dampak Kepariwisataan terhadap Erosi di Kawasan Wisata Kaliurang - Sofiudin Nurmansyah; Ambar Kusumandari; Kaharuddin Kaharuddin (Fakultas Kehutanan Universitas Gadjah Mada, 2007)
Impact of Tourism on Soil Erosion in Tourist Area of KaliurangTourism is one alternative of non timber based forest managements however, tourism activities will impact on the tourist areas, both biophysically and socially. The purpose of this research was to study the factors influencing soil erosion rate in tourist area, and to examine the effect of tourist characteristics, e.g. visiting characteristics and tourist activities on erosion rate.The erosion prediction was carried out at tourist areas including Hutan Alam (Natural Forest), Taman Bermain Anak (Play Ground), Taman Wisata Alam (Natural Tourist Park), and Kali Kuning Camping Ground. The Universal Soil Loss Equation (USLE) model was applied. Correlation analysis was used to analyze the correlation between factors influencing soil erosion rate (rainfall erosivity, soil erodibility, slopes, vegetation and conservation practices) and erosion.The research resulted that tourism significantly impacted on erosion at Play Ground, Natural Tourist Park 1, and Kali Kuning Camping Ground, except at Natural Tourist Park 2. The correlation analysis showed that all of the factors influencing soil erosion rate positively affected erosion. The results also showed that the tourist characteristics which influence erosion rate were tourists' visiting characteristics and their activities.